Beban Kerja di Era Digital: Analisis Bibliometrik Menggunakan VosViewer di Google Scholar - Hoeroni, Rizqon; Gunawan, Ahmad (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research aims to conduct a bibliometric analysis of literature related to workload in the digital era. Bibliometric analysis methods are used to explore and understand recent developments in workload research, particularly in the context of the digital era. This research collects data from primary bibliographic sources including scientific journals, conferences, and other related literature.The results of the bibliometric analysis provide an in-depth understanding of workload research trends, dominant measurement methods, as well as the significant contributions of researchers in this field. In addition, through network analysis, relationships and collaboration between researchers as well as research interdisciplinarity can be identified. The findings of this research provide valuable insight into recent developments in workload analysis in the digital era. The implications of this research can help researchers, practitioners and policy makers understand research dynamics related to workload and map potential research directions in the future. The conclusions from this bibliometric analysis can serve as a basis for developing a better understanding of workload challenges and opportunities in the changing world of work.